Nomogram-based prediction of the prognosis in patients with free floating venous thrombus after closed traumatic fracture - Yao Wei; Changxu Guo; Xiaoyu Chen; Yu Yuan (BMC Medical Imaging)
Abstract Background Free-floating venous thrombosis (FFVT), a distinct subtype of deep vein thrombosis (DVT), is associated with pulmonary thromboembolism (PTE) and carries a high mortality risk. Objective This study aimed to develop a nomogram to predict the prognosis of FFVT in patients with closed traumatic fractures. Materials and methods A retrospective analysis of clinical and ultrasound data from 326 patients with FFVT post-closed traumatic fractures was conducted. Patients were divided into training (n = 240, January 2019–June 2023) and validation (n = 86, June 2023–June 2024) sets. Prognostic risk factors were identified using LASSO and multivariable logistic regression. A nomogram was constructed using R Studio, and its predictive accuracy was validated via calibration curves, receiver operating characteristic (ROC) analysis, and external validation. Results Independent risk factors for FFVT progression to closed thrombus included D-dimer levels, FFVT location, collateral blood flow volume around the thrombus, and thrombus margins (P < 0.05). The model demonstrated high discriminative ability, with a C-index of 0.945. ROC analysis revealed areas under the curve (AUC) of 0.949 (training set) and 0.924 (validation set). Calibration curves confirmed strong agreement between predicted and observed outcomes. Conclusion The nomogram provides an accurate prognostic tool for FFVT in patients with closed traumatic fractures, aiding clinical decision-making to improve patient outcomes. Clinical trial number Not applicable.